Healing Beyond Walls: Dr. Shamoon Noushad’s Nature-Based Therapy Model for Psychophysiological Rehabilitation in Pakistan. - Saleem, Yusra (International Journal of Endorsing Health Science Research, 2025)
Pakistan faces an escalating mental-health crisis exacerbated by socioeconomic instability, post-disaster trauma, and environmental degradation. Conventional clinical resources remain insufficient to meet this growing burden, underscoring the need for evidence-based, low-cost, and culturally adaptive interventions. Clinical psychophysiologist Dr. Shamoon Noushad has advanced a novel Nature-Based Therapy (NBT) framework that integrates environmental exposure, heart-rate variability biofeedback, and guided mindfulness to restore psychophysiological balance. This editorial examines the theoretical foundations, empirical evidence, and implementation trajectory of NBT within Pakistan’s health ecosystem, positioning it as a scalable model for trauma recovery and psychosocial rehabilitation.